2013
DOI: 10.1002/app.39609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aromatic additives with various alkyl groups on orientation birefringence of cellulose acetate propionate

Abstract: Orientation birefringence and its wavelength dispersion in blends of cellulose acetate propionate (CAP) and aromatic additive molecules having various alkyl chains were investigated, in order to evaluate the effect of the chemical structure on the optical properties. We found that the additive improved the orientation birefringence of CAP, meaning that the additive orientation is parallel to CAP chains via the "nematic interaction (NI)" reflecting the intermolecular orientation correlation. The NI strength was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…. Therefore, the difference in orientation birefringence between CAP and the blend is originated from the additive orientation as examined in previous articles …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…. Therefore, the difference in orientation birefringence between CAP and the blend is originated from the additive orientation as examined in previous articles …”
Section: Resultsmentioning
confidence: 81%
“…Now, the effect of PET and PEN on birefringence is compared with that in the other polymer blends. In previous works, we reported that aromatic additives such as TCP, dioctyl phthalate (DOP), and various kinds of ester compounds enhance the birefringence of CAP. The increment by the additives was just 5 × 10 −4 at the same experimental conditions with this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, however, the molecular weight of XylAc is ten times lower than that of CTA, meaning that the difference in the orientation relaxation time is larger than that in PS/PPO system. In previous works (Nobukawa et al 2013(Nobukawa et al , 2014a, we investigated the ratio of F in cellulose acetate propionate (CAP) and ester oligomers. Although the oligomers have much lower molecular weight than the matrix CAP, the molecular orientation is consistent with the matrix CAP due to the intermolecular orientation correlation, which is called as nematic interaction (Doi et al 1989).…”
Section: Orientation Birefringence Of Stretched Filmsmentioning
confidence: 99%
“…With decreasing of the free volume, the amplitude of the local motion for beta relaxation becomes smaller (Yamaguchi and Arakawa 2007b;Nobukawa et al 2013).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%